SOCIO-ECONOMIC CORRELATES OF CULTURAL OREGANIZATION PATTERN TO IMPROVEING THE EMPLOYMENT WORK EFFICIENCY IN ADVENTIST WEST JAVA CONFERENCE. - Romulo Sinabutar (Jurnal Ekonomis, 2019)
The aims of this research are to find out how the socio economic and the organizational culture of Adventist West Java Conference to improving the employment work efficiency. This descriptive correlational study utilized questionnaires to 130 respondents. The results of the study are the following: 1) the socio economic of Adventist West Java Conference was not significantly related to the employment work efficiency, 2) the organizational culture was significantly related to the employment work efficiency, and 3) as the simultaneous that the socio economic and organizational culture are significantly related to employment work efficiency.